Sanksi Pidana Pemerkosaan Terhadap Anak Menurut Hukum Pidana Positif dan Hukum Pidana Islam - Fitri Wahyuni (Jurnal Media Hukum, 2016)
Crime is a social phenomenon that occurs at any place and time. One form of the crime is rape against children. This research is motivated by the condition of the large number of rapes that occur against children. But the threat of criminal penalties against perpetrators of child rape with imprisonment of a maximum of 15 (fifteen) years is considered not reflect the sense of justice for children as victims and that provision is not in accordance with the development of the people of Indonesia are mostly Muslim. This encourages the comparison between positive criminal law with Islamic criminal law and the need for reform of criminal law in the future. Descriptive-analytic approach-comparative, used to analyze criminal sanctions in rape against children in Indonesia. Criminal sanctions rape of children as contained in the Criminal Code and the laws establish child protection imprisonment. Viewed from the objective of sentencing in criminal law rape Indonesia that criminal sanctions against children in positive criminal law does not accommodate the interests of the protection of victims but only oriented to act so that the objective of sentencing offenders to provide a deterrent effect against perpetrators have not been up to materialize. While the Islamic criminal law does not mention explicitly about rape,  but rape in Islamic criminal law can be in groups into jarimah adultery even more cruel. Islamic law had explained that rape is hirabah (QS. Al Maidah: 33). Punishment in the form of the death penalty, crucifixion, hand cut legs crossed or exiled. Thus, the formulation of sanctions in criminal law reform on child rape can be adopted with a choice of criminal sanctions as contained in the criminal law of Islam.